Females and males exhibit similar functional, mechanical, and morphological outcomes in a rat model of posttraumatic elbow contracture. Issue 9 (2nd December 2020) - Reiter, Alex J.; Schott, Hayden R.; Castile, Ryan M.; Cannon, Paul C.; Havlioglu, Necat; Chamberlain, Aaron M.; Lake, Spencer P.
Abstract: Posttraumatic joint contracture (PTJC) is a debilitating condition characterized by loss of joint motion following injury. Previous work in a rat model of elbow PTJC investigated disease etiology, progression, and recovery in only male animals; this study explored sex‐based differences. Rat elbows were subjected to a unilateral anterior capsulotomy and lateral collateral ligament transection followed by 42 days of immobilization and 42 days of free mobilization. Grip strength and gait were collected throughout the free mobilization period while joint mechanical testing, microcomputed tomography and histological analysis were performed postmortem. Overall, few differences were seen between sexes in functional, mechanical, and morphological outcomes with PTJC being similarly debilitating in male and female animals. Functional measures of grip strength and gait showed that, while some baseline differences existed between sexes, traumatic injury produced similar deficits that remained significantly different long‐term when compared to control animals. Similarly, male and female animals both had significant reductions in joint range of motion due to injury. Ectopic calcification (EC), which had not been previously evaluated in this injury model, was present in all limbs on the lateral side. Injury caused increased EC volume but did not alter mineral density regardless of sex. Furthermore, histological analysis of the anterior capsule showed minor differences between sexes for inflammation and thickness but not for other histological parameters. A quantitative understanding of sex‐based differences associated with this injury model will help inform future therapeutics aimed at reducing or preventing elbow PTJC.